Epilobium hirsutum alters xenobiotic metabolizing CYP1A1, CYP2E1, NQO1 and GPx activities, mRNA and protein levels in rats. (26th March 2013) - Karakurt, Serdar; Semiz, Aslı; Celik, Gurbet; Gencler-Ozkan, Ayşe Mine; Sen, Alaattin; Adali, Orhan
Abstract: Context : Natural products have attracted increasing interests due to their use in flavoring, nutrition, cosmetics, pharmacy and medicine. Epilobium hirsutum L. (Onagraceae) is known for its analgesic, antimicrobial, and antiproliferative activity. CYP1A1 and CYP2E1, xenobiotic metabolizing enzymes, serve as a metabolic activation route yielding reactive metabolites that are eliminated by the action of NQO1 and glutathione peroxidase (GPx) enzymes. Objective: This study investigated in vivo effects of Epilobium hirsutum ( EH ) on CYP2E1, CYP1A1, NQO1 and GPx activities, protein and mRNA expressions in liver. Materials and methods: Male Wistar Albino rats were injected with EH at a dose of 37.5 mg/kg i.p. daily for 9 d. CYP2E1, CYP1A1, NQO1 and GPx activities, protein and mRNA levels were determined by enzyme assays, Western blotting and qPCR, respectively. Results: CYP1A1 associated ethoxyresorufin- O -deethylase activity of control and EH -treated animals were found as 6.54 ± 1.21 and 4.48 ± 1.67 nmol/min/mg, respectively. CYP2E1 associated aniline 4-hydroxylase of control and EH group were 0.537 ± 0.011 and 0.109 ± 0.01 nmol/min/mg, respectively. However, EH treatment increased the GPx and NQO1 activities from 0.069 ± 0.015 to 0.107 ± 0.026 nmol/min/mg and from 163.34 ± 92 to 588.3 ± 14 nmol/min/mg, respectively. Furthermore, protein and mRNA expression analysis revealed that CYP1A1 and CYP2E1 levels were decreased while those of NQO1 and GPx increased after EH treatment. Discussion and conclusion: Our current data suggest that the metabolism of xenobiotics, including drugs, may be altered due to changes in the expression and activity of these proteins by EH .